Sistem Mekanisme Penyuntingan Naskah Novel Chicklit dan Teenlit Indonesia Pada Tiga Penerbit - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Some literary experts say that literary works are cultural objects and production is an industrial process. When literature enters the territory of production then the laws imposed upon itself are industrial law. That is why when talking about the production of literary works means dealing with laws (read: systems, mechanisms, and strategies) imposed by the institutions of production, i.e. publishers. Whereas in industrial business competition, every producing institution besides applying the conventional laws of industry, also develops distinctive internal laws to maintain the competitive power of its institution against the strength of other producing institutions.Modern publishers as a book-producing institution must creatively develop their industrial laws to compete with other publishers of the same kind. Starting from the above references in chicklit and teenlit novel Indonesia's production article will discuss chicklit and teenlit novel production mechanism and mechanism covering three publishers, namely Elex Media Komputindo, GagasMedia, and Gramedia Pustaka Utama. The system and production mechanism referred to is in the case of editing the manuscript. The editing of the manuscript includes the selection of manuscripts, structuring of languages, arrangement of settings, and final alignment.